Suitability Analysis of Gram Staining with Blood Culture in Bacteremia - Eva Nada Maulida; Irda Handayani; Nursin Abdul Kadir (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Bacteremia is a serious bloodstream infection, requiring blood culture as the gold standard for definitive diagnosis and rational therapy, but it is time-consuming. The Gram stain should be considered as an alternative test, as it is easier and faster to determine empirical antibiotic therapy in order to minimize the use of broad-spectrum antibiotics. This study aimed to analyze the suitability of Gram staining results with blood cultures in bacteremia. Cross-sectional study design from August to September 2022 at Dr. Wahidin Sudirohusodo Hospital and Labuan Baji Hospital, Makassar. The study sample used specimens from automatic positive blood culture bottles of new bacteremia patients. Gram staining and sub-culture were performed to determine the type of Gram-positive or negative bacteria. Appropriate statistical analysis was used to compare the two methods. A total of 78 research samples were obtained. The results of subculture vs. Gram staining showed Gram-positive bacteria in 45 vs. 42 samples and Gram-negative bacteria in 33 vs. 36 samples, respectively. A comparative test using the Wilcoxon test showed no significant difference for the 2 tests, p-value = 0.257 (p > 0.05). The results of the Gram diagnostic test on culture showed high sensitivity and specificity, respectively: 88.9%, and 93.9% for Gram-positive bacteria, 93.9% and 88.9% for Gram-negative bacteria. Positive Predictive Value (PPV) and Negative Predictive Value (NPV) were 95.32% and 95.32% for Gram-positive, 86.11%, and 95.23 % for Gram-negative bacteria, respectively. There is a suitability between Gram stain and automatic blood culture results with high diagnostic value. Gram staining is expected to be a guide for selecting empirical therapy based on Gram's classification until the AST test results come out.